Peran Consumer Satisfaction pada Pengaruh Antara Dinning Experience Terhadap Revisit Intention di Café Kawasan Kavling DPR Sidoarjo - Wicaksono, Muhammad Arif; Muzdalifah, Laily (Universitas Negeri Padang, 2024)
This research contributes to knowing whether the dining experience attribute has an impact on revisittintention mediatedbby consumer satisfaction. The data in this study used a questionnaire with aasample size of 100 respondents. Therresults of this study are that the food quality variable has aasignificant effectton consumer satisfaction, the food quality variable has no significant effect on revisit intention, thesservice qualityvvariable has a significant effect on consumer satisfaction and revisit intention, the physical environment variablehhas no significant effectoon consumer satisfaction and revisit intention, the food quality and service quality variables have a significant effect on revisit intention mediated by consumer satisfaction, and the physical environment hasnno significant effect onnrevisit intention mediated by consumerssatisfaction